Hubungan Hukum Para Pihak Dalam Layanan Urun Dana Melalui Penawaran Saham Berbasis Teknologi Informasi - Ratna Hartanto (Fakultas Hukum Universitas Islam Indonesia, 2020)
The development of information technology has provided many facilities for business entities to obtain funding. One way to obtain funding without going through an initial public offering process is through equity crowdfunding. Equity crowdfunding is a platform system developed and managed by a host company. The platform can be used by publishing companies to offer securities in the form of shares to buyers or investors. Equity crowdfunding investors need legal certainty and legal protection for their investments. On the other hand, equity issuers and platform operators also need to get legal certainty from the Financial Services Authority. The Financial Services Authority has issued Financial Services Authority Regulation (POJK) Number 37/POJK.04/2018 regarding Funding Services through Information Technology Based Shares (Equity Crowdfunding). The problem examined in this paper is how the construction of legal relations and legal protection for the parties in equity crowdfunding in Indonesia. This study uses a normative method by reviewing the laws and regulations related to the legal issues studied. The results of the study concluded that the parties in holding equity crowdfunding, namely share issuers, organizers, and investors, all three has a triangular relationship that is born based on agreements or laws and regulations. Even though the OJK has issued regulations relating to equity crowdfunding, the current regulations do not guarantee full legal protection especially for investors.